Subject stages in student-centered learning - RUSOV, Veronica (Acta et commentationes: Științe ale Educației, 2023)
The article falls into the issue of student-centered higher education. According to different authors, the stages that the student goes through in order to become the subject of their own professional training path are analyzed theoretically. The article presents the comparative results of an empirical study, obtained on a sample of students from I-IV years of pedagogical specialties. The findings demonstrate that the subject stages of learning were recorded only in the fourth year students.